DAMPAK INTERVENSI PENDIDIKAN "GI-PSI-SEHAT" BAGI IBU TERHADAP KONSUMSI PANGAN DAN STATUS GIZI ANAK USIA DINI - Madanijah, Siti (GIZI INDONESIA, 2004)
THE IMPACT OF EDUCATION MODEL “GI-PSI-SEHAT” (NUTRITIONPSYCHOSOSIAL-HEALTH) FOR MOTHER ON FOOD CONSUMPTION AND NUTRITIONAL STATUS OF CHILDREN UNDER TWO YEARThe objective of this study is to develop and to analyze the education wholistic model (NutritionPsychosocial-Health) in order to build good food consumption pattern for children through theimprovement of mother’s behaviour. A quasi experiment, nonrandomized control group pretest -posttest design study, of the impact of the education model “GI-PSI-SEHAT” (NutritionPsychosocial-Health) has been carried out at urban area in Bogor, West Java. The total ofrespondent are 131 primiparous mothers of children of 0-11 months, who are selected bypurposive sampling technique, which consist of 66 mothers in control group and 65 mothers inintervention group, who participated in the intervention programme. During five months, educationmodel “GI-PSI-SEHAT” was conducted by face to face method, in groups or individually, withcombination of teaching techniques i.e. speech, discussion, simulation, practical and home visit.Teaching aids i.e. booklets, flip-chart, food-models, and real things was used in order to increasethe effectiveness of the programme. The study reveals that the intervention of “GI-PSI-SEHAT”improves food consumption pattern, whether in punctuality, food diversification, or the frequency offood consumption. In eight months time, the intervention enable the increase of the MeanAdequacy Ratio (MAR) as an overall measure of the nutrient adequacy. The impact of theintervention of “GI-PSI-SEHAT” is decrease of z-score of weight-for-age and height-for-age of theintervention group is lower than the control group, especially for children under 12 month.Classification and regression tree statistical analysis demonstrated that independent variableshave strong association with response variables. Nutritional status of mother based on Body MassIndex (BMI) is the dominant variable associated with nutritional status of children based on z-scoreof weight for age, on the other hand Mean Adequacy Ratio (MAR) is the dominant variableassociated with nutritional status of children based on z-score of height for age. Wholisticeducation model “GI-PSI-SEHAT” for mothers with some modification may applicable at anotherarea, especially for community with low education level.Keywords: nutrition education, children under two years, complementary feeding, food consumption pattern, nutritional status.